МАТЕМАТИЧНА МОДЕЛЬ ГНУЧКОЇ МІКРОМЕРЕЖІ, ІНТЕГРОВАНОЇ ДО ЕНЕРГОСИСТЕМИ - Саух, С.Є.; Борисенко, А.В. (Інститут електродинаміки НАН України, Київ, 2023)
The functioning of local electric networks ('Micro Grid') is described, which due to the development of Smart Network technologies, distributed generation and electricity storage systems received an incentive for development. The structural decomposition of the market model is suggested for the 'Top-Level Market' and 'Micro Grid' local systems to reflect the interaction of the 'Micro Grid' with the wholesale electricity market. Load regulation instruments are described, which ensure the flexibility of the Micro Grid. A mathematical model of the 'Micro Grid' system is proposed, which formulated as a Unit commitment problem. The computational experiment shows the adequacy of the results of modelling of 'Micro Grid' systems. References 9, figures 4, tables 2.